Enjoy it! Cosmetic try-on apps and augmented reality, the impact of enjoyment, informativeness and ease of use - Micheletto, V.; Accardi, S.; Fici, A.; Piccoli, F.; Rossi, C.; Bilucaglia, M.; Russo, V.; Zito, M. (Frontiers in Virtual Reality, 2025)
Virtual Try-On cosmetics apps based on Augmented Reality (AR) technology can improve both consumer product evaluation and purchase decisions, while also supporting companies’ marketing strategies. This study explores the factors influencing the use of AR-based cosmetics apps by administering the Technology Acceptance Model (TAM) and additional scales on a sample of 634 Italian consumers. Perceived Informativeness (PI) and Perceived Ease of Use (PEOU) were hypothesized as predictors of TRUST, DOUBT, Makeup Involvement (MI), Perceived Diagnosticity (PD), and Behavioral Intention (BI), with Perceived Enjoyment (PE) acting as a mediating variable. The structural equation model (SEM) confirmed PI as a strong predictor, with PE serving as a key mediator. The findings suggest that a moderate level of PE and PEOU is ideal - excessive simplicity or playfulness increases DOUBT and decreases TRUST. Both PD and BI are positively affected by the AR experience, with their coexistence being crucial for effective app usage. Additionally, PI, mediated by PE, significantly influences BI, emphasizing the role of information in consumer decision-making. These results provide valuable insights for the cosmetics industry, offering guidance to refine user experiences and enhance consumer engagement and satisfaction.